Relavansi Partai Politik dalam Pelaksanaan Pemilu dan Pilkada dalam Konsep Demokrasi Parlementer - Mustajib Mustajib (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The existence of political parties in a country that adheres to a democratic system is a necessity and the inevitability of their existence. Because with the existence of political parties, democracy will run according to the reel that it should run, starting from the freedom to gather and associate as regulated in the constitution to the implementation of general elections for President and Vice President, Legislative and regional head elections indicating that democracy in a country is at least whether or not it can be said to be going well. In Indonesia itself, the existence of political parties can be said to be multi-party because there are more than two parties, as in several other democratic countries where there are only two parties. Although in general, if we look at their ideology, political parties in Indonesia can be grouped into just two, namely parties that are religiously oriented (religious) and parties that are nationalist (state) oriented. In the research results, it is stated that multi-party parties do not always work well and are relevant, so there needs to be simplification in the future so that people are not confused by many parties.